Role strain among male RNs in the critical care setting: Perceptions of an unfriendly workplace. (December 2017) - Carte, Nicholas S.; Williams, Collette
Abstract: Purpose: Traditionally, nursing has been a female-dominated profession. Men employed as registered nurses have been in the minority and little is known about the experiences of this demographic. The purpose of this descriptive, quantitative study was to understand the relationship between the variables of demographics and causes of role strain among male nurses in critical care settings. The Sherrod Role Strain Scale assesses role strain within the context of role conflict, role overload, role ambiguity and role incongruity. Data analysis of the results included descriptive and inferential statistics. Inferential statistics involved the use of repeated measures ANOVA testing for significant difference in the causes of role strain between male nurses employed in critical care settings and a post hoc comparison of specific demographic data using multivariate analyses of variance (MANOVAs). Results: Data from 37 male nurses in critical care settings from the northeast of the United States were used to calculate descriptive statistics standard deviation, mean of the data analysis and results of the repeated ANOVA and the post hoc secondary MANOVA analysis. The descriptive data showed that all participants worked full-time. There was an even split from those participants who worked day shift (46%) vs. night shift (43%), most the participants indicated they had 15 years or more experience as an registered nurse (54%). Significant findings of this study include two causes of role strain in male nurses employed in critical care settings which are: role ambiguity and role overload based on ethnicity. Conclusion: Consistent with previous research findings, the results of this study suggest that male registered nurses employed in critical care settings do experience role strain. The two main causes of role strain in male nurses are role ambiguity and role overload.